Ethnoscience Learning Using “Rujak Cingur” to Enhance Fifth-Grade Elementary School Students’ Understanding of the Digestive System: A One-Group Pretest-Posttest Design - Badriatus Sa'idah; Suryanti Suryanti; Binar Kurnia Prahani; Neni Mariana; Ari Metalin Ika Puspita (Perkumpulan Dosen Tarbiyah Islam, Indonesia, 2026)
Low conceptual understanding of science among Indonesian elementary school students and the prevalence of unhealthy eating habits represent interrelated critical issues. This study was motivated by a research gap in the literature: ethnoscience studies on the digestive system remain limited to conceptual exploration or employ other cultural objects (herbal medicine, water ketupat), and no quantitative empirical evidence exists regarding the application of rujak cingur in its region of origin, Surabaya. This research aimed to examine the effect of rujak cingur-based ethnoscience learning on the conceptual understanding of the digestive system among fifth-grade students at SDN Kaliasin VII/286. A pre-experimental one-group pretest-posttest design was selected due to the limitation of having only one class population (n=23), rendering a control group unavailable, and the study's orientation as a preliminary investigation to test the intervention's potential. The findings revealed an increase in the average conceptual understanding scores from 44.83 (pretest) to 84.65 (posttest). The N-Gain analysis yielded a value of 0.72 (high category), with the mastery learning percentage rising substantially from 17.4% to 82.6%. The Wilcoxon Signed-Rank Test produced a p-value of 0.000 (p < 0.05), indicating a significant difference, with all 23 students (100%) demonstrating score improvements (Positive Ranks) and a Cohen's d effect size classified as very large (d > 1.8). These findings confirm that the implementation of rujak cingur-based ethnoscience significantly enhances the conceptual understanding of the digestive system among fifth-grade students. Theoretically, this study strengthens Ausubel's meaningful learning theory by demonstrating that concrete cultural objects can function as advance organizers, while simultaneously enriching the Culturally Responsive Teaching framework through quantitative empirical evidence. Practically, this learning model can be adopted by teachers as a contextual, affordable, and accessible alternative, supporting the preservation of local wisdom and implementing the Merdeka Curriculum through strengthening the Pancasila Student Profile dimensions of global diversity and sustainable lifestyles.